2015
DOI: 10.1007/s10995-015-1743-9
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Disrespect and Abuse During Childbirth and Women’s Confidence in Health Facilities in Tanzania

Abstract: Our study highlights disrespectful and abusive treatment during childbirth as an important factor in reducing women's confidence in health facilities. Improving interpersonal care must be an integral part of quality improvement in maternal health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
127
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(140 citation statements)
references
References 35 publications
7
127
4
2
Order By: Relevance
“…A recent systematic review synthesized global evidence on mistreatment during childbirth, and presented a new typology to describe the phenomenon [7]. This review built on other work in the field, including a landscape analysis [8] and primary studies in Kenya, Tanzania and Nigeria [911]. In Guinea, anecdotal evidence suggests that women across the country experience mistreatment during childbirth.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review synthesized global evidence on mistreatment during childbirth, and presented a new typology to describe the phenomenon [7]. This review built on other work in the field, including a landscape analysis [8] and primary studies in Kenya, Tanzania and Nigeria [911]. In Guinea, anecdotal evidence suggests that women across the country experience mistreatment during childbirth.…”
Section: Introductionmentioning
confidence: 99%
“…For example this may include slapping, pinching, verbal abuse, lack of privacy and discrimination [3]. In recent years, evidence from several sub-Saharan African countries, including Tanzania [4, 5], Kenya [6, 7], Nigeria [8] and Ghana [9–11], suggests that mistreatment during childbirth may be a common occurrence, and may be exacerbated by certain characteristics of the woman, including age and HIV status. This work has been groundbreaking to better understand women’s experiences of mistreatment during childbirth, as well as efforts to measure mistreatment that does occur, through observations of labor and childbirth, and follow-up surveys with women.…”
Section: Introductionmentioning
confidence: 99%
“…Sub-standard quality of care contributes towards maternal mortality; for example, a study assessing all maternal deaths in tertiary care hospitals in Sri Lanka found that the majority of maternal deaths were preventable, with 79 % attributable to substandard care [7]. Beyond poor health outcomes, a study in Tanzania suggests that women who experience disrespectful or abusive care reported less satisfaction with their delivery, perceived quality of care for delivery, and were less likely to deliver in the same facility [8]. Analyses suggest that were respectful care and availability of drugs/equipment to improve, that the proportion of women preferring a facility delivery would increase from 43 to 88 % [5].…”
Section: Introductionmentioning
confidence: 99%